The role of principal leadership in improving education quality - Palangda, Listriyanti; Rawis, Joulanda AM; Tambingon, Henny N.; Kambey, Joseph (International Journal of Curriculum Development, Teaching and Learning Innovation, 2023)
This writing has the main objective of knowing the leadership role of the principal in improving the quality of education. The quality of education is our hope in facing the exchange of life that in several sectors, especially in the field of education sector for a better future. In order to realize quality education, this needs to be done leadership role in educational institutions. One of them is the principal because of that is a pioneer who drives all changes towards quality education. The research method used is the qualitative method. The data collection techniques used were observation, interviews, documentation and data triangulation, while the informants in this study were the principal, deputy principal and two teachers. The results showed that the principal of SMP 5 Tondano had carried out his role well in terms of quality planning, quality control and quality improvement of education at SMP 5 Tondano.